A 6/5/5/7 heterotetracyclic indole derivative alkaloid isolated from Typhonium giganteum. Issue 7 (13th February 2020) - He, Da-Hai; Chen, Jun-Xian; Fu, Xian; Guo, Da-Le; Xia, Bing; Liu, Guang-Hui; Ding, Ke-Yi; Fang, Dong-Mei; Zhou, Yan
Graphical abstract: Highlights: Typhoniumoid A (1 ) was a new skeleton type alkaloid which was similar to carboline. Typhoniumoid A (1 ) possessed a 6/5/5/7 heterotetracyclic and 7, 5-spirocyclic moiety. Typhoniumoid A (1 ) isolated from Typhonium giganteum Engl. The structure was elucidated by the analyses of NMR and ECD calculations. Abstract: Typhoniumoid A (1 ), a new skeleton type alkaloid which was similar to carboline, possessed a 6/5/5/7 heterotetracyclic fused coupling with an unprecedented 7, 5-spirocyclic moiety was isolated from Typhonium giganteum Engl. The structure was completely elucidated by combination of diverse methods which include one and two dimensional NMR, and ECD calculations.